2018
DOI: 10.1186/s12879-018-3241-3
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary results of official influenza and acute respiratory infection surveillance in two towns of Burkina Faso, 2013–2015

Abstract: BackgroundIn 2010, influenza, influenza-like illness (ILI) and acute respiratory infection (ARI) surveillance was established by the government of Burkina Faso. We provide preliminary descriptive results from this surveillance activity.MethodsThe study period was 2013 through 2015. Two primary healthcare facilities in Bobo-Dioulasso district reported ILI in outpatients. Influenza virology, using reverse transcription-polymerase chain reaction (rRT-PCR), was available for a proportion of ILI patients. One hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 27 publications
(27 reference statements)
2
9
0
Order By: Relevance
“…We found that influenza virus was predominating among ILI cases over the six-year period, accounting for more than 22% of all tested samples. This is similar to other reports in which influenza frequency ranged from 14.8% to 30.9% [8,10,15,16,[18][19][20]. Moreover, among typed influenza positive samples, the majority were type A, reaching 77.1%.…”
Section: Discussionsupporting
confidence: 91%
“…We found that influenza virus was predominating among ILI cases over the six-year period, accounting for more than 22% of all tested samples. This is similar to other reports in which influenza frequency ranged from 14.8% to 30.9% [8,10,15,16,[18][19][20]. Moreover, among typed influenza positive samples, the majority were type A, reaching 77.1%.…”
Section: Discussionsupporting
confidence: 91%
“…In Burkina Faso, a country in the semiarid Sahel and Savanna zones of West Africa, malaria transmission remains high, with marked seasonality in the rainy season [9e11]. Influenza virus has been reported to circulate in Burkina Faso [12,13], but its importance and that of other viral respiratory infections in the aetiology of nonmalaria fever remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…These data covered aspects of influenza detection and seasonality. 21 countries reported influenza surveillance data among inpatients with severe acute respiratory infection (SARI) and outpatients with influenza-like-illness (ILI) 6 , 13 , 19 , 26 , 27 , 30 , 32 , 33 , 36 , 37 , 40 , 45 , 46 , 51 , 55 , 61 , 64 , 69 , 70 , 72 ; whereas Gabon, Togo, Burkina Faso, Central Africa Republic and Uganda reported influenza surveillance data among outpatients with ILI only 14 , 17 , 18 , 60 , 73 , 154 .…”
Section: Resultsmentioning
confidence: 99%
“…These data covered aspects of influenza detection and seasonality. 21 countries reported influenza surveillance data among inpatients with severe acute respiratory infection (SARI) and outpatients with influenza-like-illness (ILI) 6,13,19,26,27,30,32,33,36,37,40,45,46,51,55,61,64,69,70,72 ; whereas Gabon, Togo, Burkina Faso, Central Africa Republic and Uganda reported influenza surveillance data among outpatients with ILI only 14,17,18,60,73,154 . Globally, the case definition used in most surveillance systems was consistent with that of WHO for influenza-like illness (defined as an acute respiratory infection with measured fever of ≥ 38°C, and cough, with onset within the last 7 or 10 days), or severe acute respiratory infection (defined as an acute respiratory infection with history of fever or measured fever of ≥ 38°C, and cough, with onset within the last 7 or 10 days, and requiring hospitalization) 18,26,28,30,32,49 .…”
Section: Influenza Surveillancementioning
confidence: 99%